2011
DOI: 10.1007/s00449-011-0623-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biological nitrogen removal in MLE combined with post-denitrification process and EF clarifier

Abstract: A modified ludzack ettinger reactor (MLE) combined with a post-denitrification reactor (PDMLE) using electroflotation (EF) as a secondary clarifier was investigated on its feasibility and process performance. Results indicated that higher mixed liquor suspended solids (MLSS) concentrations in bioreactor (5,350 ± 352 mg L(-1)) were maintained via the highly concentrated return sludge (16,771 ± 991 mg L(-1)) from the EF clarifier and the effluent suspended solids (SS) concentrations continued relatively low, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…However, in 17.48% of the analyzed samples, the residual bioavailable organic matter in the effluent was insufficient, thus limiting the heterotrophic denitrification process, the most extensively applied process in WWTP because of its high efficiency and simplicity . In spite of this fact, the denitrification of wastewater always occurred successfully, indicating a possibility of endogenous denitrification, as previously reported in other studies . Figure depicts an inverse correlation of the C/N ratio with nitrification and denitrification rates, with a determination coefficient ( R 2 ) lower for the nitrification (0.856) than for the denitrification rate (0.987).…”
Section: Resultssupporting
confidence: 59%
“…However, in 17.48% of the analyzed samples, the residual bioavailable organic matter in the effluent was insufficient, thus limiting the heterotrophic denitrification process, the most extensively applied process in WWTP because of its high efficiency and simplicity . In spite of this fact, the denitrification of wastewater always occurred successfully, indicating a possibility of endogenous denitrification, as previously reported in other studies . Figure depicts an inverse correlation of the C/N ratio with nitrification and denitrification rates, with a determination coefficient ( R 2 ) lower for the nitrification (0.856) than for the denitrification rate (0.987).…”
Section: Resultssupporting
confidence: 59%
“…Biological nitrogen removal (BNR) is one of the most effective and economic technologies for treating domestic wastewater, generally achieved with pre-or post-denitrification. 1 In municipal wastewater treatment plants (WWTPs), pre-denitrification, anaerobic-anoxic-oxic (A 2 O) or University of Cape Town process (UCT), can utilize the available carbon source in the influent for translating nitrate (NO 3 − -N) to dinitrogen in the anoxic zone. 2 However, it needs to recirculate the nitrified liquid from the oxic zone, limiting the nitrogen removal efficiency to 60-70%.…”
Section: Introductionmentioning
confidence: 99%
“…But too high DO concentration may lead to inefficient sludge settle-ability and bad nitrogen removal. As a consequence, lots of studies on aeration optimization [6][7][8] and low DO technology [9] had been done recently for cutting energy consumption. In southern China, most of WWTPs lack the automatic control and regulation devices, so that DO concentration in aeration tank always keeps high condition during the rainy season when influent wastewater characteristics are defined as the low concentrations of pollutants and flow fluctuation [8][9][10].…”
Section: Introduction Rmentioning
confidence: 99%
“…As a consequence, lots of studies on aeration optimization [6][7][8] and low DO technology [9] had been done recently for cutting energy consumption. In southern China, most of WWTPs lack the automatic control and regulation devices, so that DO concentration in aeration tank always keeps high condition during the rainy season when influent wastewater characteristics are defined as the low concentrations of pollutants and flow fluctuation [8][9][10]. Some researchers reported that excessive aeration could inhibit TP removal performance [11][12][13], but the mechanism was not clearly stated.…”
Section: Introduction Rmentioning
confidence: 99%